NADPH-Oxidase, Rho-Kinase and Autophagy Mediate the (Pro)renin-Induced Pro-Inflammatory Microglial Response and Enhancement of Dopaminergic Neuron Death - Andrea Lopez-Lopez; Begoña Villar-Cheda; Aloia Quijano; Pablo Garrido-Gil; María Garcia-Garrote; Carmen Díaz-Ruiz; Ana Muñoz; José L. Labandeira-Garcia (MDPI AG, 2021)
Dysregulation of the tissue renin-angiotensin system (RAS) is involved in tissue oxidative and inflammatory responses. Among RAS components, renin, its precursor (pro)renin and its specific receptor (PRR) have been less investigated, particularly in the brain. We previously showed the presence of PRR in neurons and glial cells in the nigrostriatal system of rodents and primates, including humans. Now, we used rat and mouse models and cultures of BV2 and primary microglial cells to study the role of PRR in microglial pro-inflammatory responses. PRR was upregulated in the nigral region, particularly in microglia during the neuroinflammatory response. In the presence of the angiotensin type-1 receptor blocker losartan, to exclude angiotensin-related effects, treatment of microglial cells with (pro)renin induces the expression of microglial pro-inflammatory markers, which is mediated by upregulation of NADPH-oxidase and Rho-kinase activities, downregulation of autophagy and upregulation of inflammasome activity. Conditioned medium from (pro)renin-treated microglia increased dopaminergic cell death relative to medium from non-treated microglia. However, these effects were blocked by pre-treatment of microglia with the Rho-kinase inhibitor fasudil. Activation of microglial PRR enhances the microglial pro-inflammatory response and deleterious effects of microglia on dopaminergic cells, and microglial NADPH-oxidase, Rho-Kinase and autophagy are involved in this process.